Risk Analysis of Community Water Quality in Alahan Panjang Agricultural Area, Solok Regency, West Sumatera, Indonesia - Sari Arlinda; Suksmerri Suksmerri; Mukhlis Mukhlis; Mahaza Mahaza (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: Pesticides are chemicals used by farmers to eliminate pests on plants and increase crop productivity. The intensive use of pesticides increases pesticide residues in soil and water. Pesticides can cause certain cancers such as cancer of the digestive system, stomach, esophagus, lung, intestine, bladder, and lymphoma, mutagenic, and teratogenic. The purpose of this research was to determine the risk analysis of community water quality in the agricultural area of Alahan Panjang, Solok Regency. Methods: The design applied in this research was a descriptive observational study conducted with a cross-sectional design and a field study approach with Environmental Health Risk Analysis (EHRA), by examining30 dug wells in the agricultural area of Alahan Panjang and the people who consume the water taken by purposive sampling. Results and Discussion: The average length of use of well water by the community was 26.87 years. Based on the results of sanitation inspections, most of the well water was vulnerable to contamination, namely 90%. All well water samples exceeded the quality standard value of 0.1 mg/L. All real-time Risk Quotient (RQ) and 30 year RQ values were risky. Conclusion: The use of pesticides that were not in accordance with the established rules causes pollution to the water sources consumed by the community around the Alahan Panjang farm. The excessive use of pesticides can cause contamination of water sources in communities around agricultures areas.